Matchless organization : the Confederate Army Medical Department - Hasegawa, Guy R. (Engaging the Civil War., 2021)
"'Matchless Organization' describes the operations of the Confederate Army's Medical Department as managed by its successive surgeons general, especially Samuel Preston Moore"--